Rotifer (microzooplankton) production through NPK fertilization - Sharma, O P; Saini, V P (Indian Journal of Fisheries, 2011)
The young stages (spawn) of fish prefersmall feed, particularly rotifers. Encouragingresults of zooplankton production by usingNPK mixture for pond fertilization have beenobtained in different parts of the world (TennerI960;.Prowse 1967, Rabanall967). Thepresent investigation was carried out with locallyavailable NPK mixture having ratio of18:18:10. Special emphasis was to obtainhigher population of rotifers under local environmentalconditions.